Towards a Pacific Island sociology of sport : seeking new horizons - Kanemasu, Yoko (Research in the sociology of sport, 2024)
Engaging with critical gaps and building on existing knowledge, this volume of Research in the Sociology of Sport brings to the fore new stories from across Oceania, extending the horizon of regional sport scholarship beyond the Global North and tackling the ever-critical question of global disparity and sport. Taking stock of existing knowledge and sociological relevance, contributors reveal the latest research on the sports and issues most widely studied in the region to date, such as sport migrations in rugby unions and sport for development. Presenting insights from emerging research on indigenous or 'traditional' sports such as indigenised cricket, outrigger canoeing and indigenous physical activities/games, chapters fill a lacuna in existing scholarship with a further emphasis on women's football, minority ethnic women's engagement with sport/exercise and ethnic politics in sport. Positioning these narratives as fundamental to the central project of the sociology of sport, rather than simply an exercise in inclusion, Towards a Pacific Island Sociology of Sport offers an exciting opportunity for sociology of sport scholars to widen the scope of their research in search of fuller understandings of the forms, meanings, dynamics and impacts of sport for Pacific peoples.